Beyond the Science-Religion Dichotomy: A Study of Ustad Abdul Somad’s Thought on the Integration of Islam and Science - Najwa Nazwah kamila; Izza Azzmi Naufal; Muh. Ilzam Faqih; Marsya Khairunnisa; Nouval Miqdad; Dwi Raharjo (TATHO: International Journal of Islamic Thought and Sciences, 2026)
The main focus of this research is to understand how Ustadz Abdul Somad (UAS) integrates the values of science and religion in the context of education and public understanding. In this research, it refers to Ian G. Barbour's theory that divides the relationship between science and religion into four typologies: conflict, independence, dialog, and integration. With this approach, the analysis of UAS in bridging science and religion can be done in more depth. The research findings show that  UAS views the Qur'an as a source of inspiration and scientific validation. He gives examples of how verses in the Qur'an can be interpreted from a scientific perspective, and highlights the concept of "scientific miracles" contained therein. Research underscores the importance of integrating science and religion in education to empower society to face the challenges of the modern era.